THE TRANSFORMATION OF LEARNING IN THE DIGITAL ERA: A THEORETICAL REVIEW OF TECHNOLOGY INTEGRATION IN EDUCATION - Rahman (Indonesian Journal of Education and Science, 2025)
The transformation of learning in the digital era has become a significant issue in contemporary education, in line with the continuous advancement of technology. This study aims to examine the integration of technology in education and its impact on the learning process. The main focus of this research is to understand how technology can be applied in educational contexts to enhance the quality of learning and student engagement. The method used in this study is a qualitative approach with a literature review design and thematic analysis. Data were collected through a review of various articles, journals, and research reports related to technology integration in education. Data analysis was conducted by identifying key themes emerging from the literature review and comparing relevant research findings. The results indicate that although technology offers great potential for improving learning, major challenges remain, such as unequal access, teacher readiness, and the lack of ongoing professional development. Nevertheless, technology integration can enhance student engagement and enable more flexible, 21st-century competency-based learning. The conclusion of this study emphasizes that the success of technology integration in education highly depends on infrastructure readiness, supportive policies, and continuous teacher training. This research also opens opportunities for further studies on the long-term impacts of digital transformation in learning.